Comparison of antegrade versus retrograde facial nerve dissection in cases of superficial parotidectomy for pleomorphic adenoma of parotid gland - B., Mundada Ashishkumar; S., Pradeep P. (International Surgery Journal, 2018)
Background: Pleomorphic adenoma being the most common benign tumor of the major salivary gland, parotid in particular, attracts attention. Facial nerve anatomically separates the superficial lobe from deeper lobe. Superficial Parotidectomy, commonly practiced surgical technique carries high risk of nerve injury causing long term functional and esthetic deficits. This prospective study was to designed to compare required time of surgery and facial nerve injury in antegrade versus retrograde dissection. Methods: Total of 32 patients who underwent superficial parotidectomy between June 2010 to June 2013 included in this study in which 18 patients were in retrograde dissection group and 14 subjects were in antegrade facial nerve dissection group. Time from the incision till closure is noted along with post operative facial nerve palsy for statistical analysis. Results: This study shows that retrograde facial nerve dissection in superficial parotidectomy requires statistically significant lesser time duration with no difference in facial nerve injury when compared to antegrade nerve dissection. Conclusions: This study approves retrograde facial nerve dissection over antegrade nerve dissection in cases of superficial parotidectomy for betterment of the patient.